Highly efficient sulfimidation of 1,3-dithianes by Cu(I) complexes - Giribabu, Lingamallu; Singh, Surya P.; Patil, Nandkumar M.; Kantam, M. Lakshmi; Gupte, Sunil P.; Chaudhari, Raghunath V. (Synthetic Communications, 2008)
A series of four Cu(I) complexes were tested for sulfimidation of 1,3-dithianes in the presence of [N-(p-tolysulfonyl)imino]phenyliodinane (PhI = NTs) as the nitrene-transfer agent. Cu(TMPhen)(PPh3)Br is an efficient catalyst with more than 90% yield of the corresponding product with less reaction time as compared to the literature copper(I) complexes.
Keywords: 1; 3-dithianes; Cu(I) complexes; PhI = NTs; sulfimidation